2004
DOI: 10.1088/0953-8984/16/30/001
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation studies of the Fe3O4/MgO (100) heteroepitaxial system grown by magnetron sputtering

Abstract: PACS numbers:68.55Jk: Structure and morphology; thickness; crystalline orientation and texture 81.15Cd: Deposition by sputtering 75.50Bb: Fe and its alloys Detailed strain relaxation studies on epitaxial magnetite, Fe 3 O 4 , films on MgO (100) substrates grown by magnetron sputtering reveal the accommodation of strain up to 600 nm thickness, a thickness much above the critical thickness (t c ) predicted by theoretical models. The results are in agreement with the suggestion that the excess strain in Fe 3 O 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
(33 reference statements)
2
29
1
Order By: Relevance
“…We have recently studied the strain status in epitaxial Fe 3 O 4 films grown on ͑100͒MgO substrate. 25 We have established that the films retain the fully strained status at the thickness much in excess of the critical thickness ͑for Fe 3 O 4 / MgO hetroepitaxial system, the estimated critical thickness for strain relaxation on the basis of the widely used Mathew and Blakeslee model is 60 nm͒ 26 values. Therefore, the present study exploited the avenue of changing the local strain in the Fe 3 O 4 film by SHI irradiation.…”
Section: Resultsmentioning
confidence: 94%
“…We have recently studied the strain status in epitaxial Fe 3 O 4 films grown on ͑100͒MgO substrate. 25 We have established that the films retain the fully strained status at the thickness much in excess of the critical thickness ͑for Fe 3 O 4 / MgO hetroepitaxial system, the estimated critical thickness for strain relaxation on the basis of the widely used Mathew and Blakeslee model is 60 nm͒ 26 values. Therefore, the present study exploited the avenue of changing the local strain in the Fe 3 O 4 film by SHI irradiation.…”
Section: Resultsmentioning
confidence: 94%
“…This is confirmed by the presence of the hysteresis in the temperature dependencies of magnetization and resistivity. In our recent study 40 we have shown that the presence of APBs affects the elastic property of the films and enables them to maintain a fully strained state up to thickness much greater than those estimated from the mismatch strain, as there is compressive strain at the domain boundaries. Because of the highly directional nature of step edge induced APBs in the films grown on vicinal substrates the elastic properties of the film will be anisotropic.…”
Section: Resultsmentioning
confidence: 99%
“…14,15,16,17,18,19 There are quite a few works on NiO/Fe 3 O 4 bilayers and multilayers, mostly grown on MgO, investigating the structural properties of the heterostructures and the nature of exchange interaction between magnetite and (the antiferromagnetic) nickel oxide. 13,20,21,22 Thin magnetite films grown on SrTiO 3 (001) allow tuning the conductivity via Nb-doping, which is of interest for some important applications.…”
Section: Introductionmentioning
confidence: 99%